Primary stapedotomy in children with otosclerosis: A prospective study of 41 consecutive cases. (28th May 2015) - Vincent, Robert; Wegner, Inge; Vonck, Bernard M. D.; Bittermann, Arnold J.; Kamalski, Digna M. A.; Grolman, Wilko
Abstract : Objectives/Hypothesis: To prospectively evaluate hearing outcomes in children with otosclerosis undergoing primary stapes surgery. Study Design: A nonrandomized, nonblinded, prospective case series. Methods: Thirty‐four consecutive pediatric patients who underwent 41 primary stapedotomies for otosclerosis in a tertiary referral center were included. Patients were included when there was evidence of otosclerotic stapes fixation and they had available postoperative pure‐tone audiometry. Patients underwent primary stapedotomy with vein graft interposition and reconstruction with a regular piston, bucket handle prosthesis, or total ossicular replacement prosthesis. Hearing results were evaluated using pre‐ and postoperative four‐frequency (0.5, 1, 2, and 4 kHz) audiometry. Air‐conduction thresholds, bone‐conduction thresholds, and air‐bone gaps were measured. Postoperative audiometry was performed at 3, 6, 9, 12, 18, and 24 months after surgery and at a yearly interval thereafter. Results: Overall, a postoperative air‐bone gap closure of 10 dB or less was achieved in 93% of cases and to within 20 dB in 98% of cases. Mean gain in air‐conduction threshold was 23 dB for the entire case series, and mean air‐bone gap closure was 23 dB. Postoperative sensorineural hearing loss, defined as changes in bone‐conduction thresholds exceeding 10 dB, occurred in one case at last follow‐up. The bone‐conduction threshold deteriorated 13 dB in this case. Conclusion: Primary stapedotomy is a safe and feasible treatment option in children with juvenile otosclerosis. Level of Evidence: 4. Laryngoscope, 126:442–446, 2016